Association between the rs3802201 polymorphism of the lncRNA MIR2052HG gene and the risk of recurrent miscarriage in a Southern Chinese population. Issue 1 (14th December 2021) - Mai, Hanran; Cai, Canhong; Lin, Kun; Zhang, Linyuan; Wang, Yishuai; He, Menghua; Qu, Yanxia; Xu, Yufen; Fu, Lanyan; Pi, Lei; Zhou, Huazhong; Zeng, Dingke; et al.
Abstract: Background: Plenty of studies have indicated that some genetic polymorphisms of the breast cancer which associated with its susceptibility may also be related to the susceptibility of abortion. MIR2052HG plays an important role in the onset and progression of breast cancer by maintaining the level of ERα, but to the best of our knowledge, the correlation between risk of recurrent abortion and MIR2052HG rs3802201 C>G polymorphism is still unclear. Therefore, we conducted this case‐control study to investigate whether MIR2052HG rs3802201 C>G polymorphism is associated with susceptibility of recurrent miscarriage (RM). Methods: We recruited 392 healthy controls and 248 patients with RM to process this research, the participants were all from southern China, and genotyping was performed by TaqMan method. Results: Our results showed that there was no evidence indicates the MIR2052HG rs3802201 C>G is related to RM (CG and CC: adjusted OR = 0.970, 95% CI = 0.694–1.355, p = 0.8577; GG and CC: adjusted OR = 0.743, 95% CI = 0.416–1.330, p = 0.3174; dominant model: adjusted OR = 0.925, 95% CI = 0.672–1.272, p = 0.6298; recessive model: adjusted OR = 0.751, 95% CI = 0.430–1.321, p = 0.3233). Conclusion: We verified that the MIR2052HG rs3802201 C>G allele might be uncorrelated to the RM risk, but these findings require further validation in multicenter studies with larger sample size and different ethnicities. Abstract : We recruited 248 women which were diagnosed with recurrent miscarriage (RM) as the RM group and included 392 age‐matched healthy controls with at least two normal pregnancies and no history of miscarriage as the control group. By TaqMan method, we compared the frequency of rs3802201 between control group and current miscarriage group, and we found out that rs3802201 has no significant association with RM.